2023
DOI: 10.1002/gps.5994
|View full text |Cite
|
Sign up to set email alerts
|

Management of cognitive frailty: A network meta‐analysis of randomized controlled trials

Yu Zhang,
Jing‐Jing Zhou,
Xu‐Ming Zhang
et al.

Abstract: ObjectivesWe aimed to compare the effectiveness of interventions in cognitive function and frailty status and rank these interventions.MethodsData Sources‐We searched PubMed, Embase, CINAHL, PsycINFO, Web of Science, Cochrane Library, Central Register of Controlled Trials (CENTRAL), CNKI, Wanfang, VIP and Google scholar. Data synthesis‐The risk of bias was assessed using the Cochrane risk bias assessment tool. Statistical heterogeneity was assessed using the Chi‐square test and quantified by I2. The results we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…The latest network meta-analysis reveals that CF multicomponent exercises may be the most effective strategies to improve cognitive function and frailty. 59 Future randomised controlled trials should be designed and evaluated based on both effectiveness and feasibility. Due to cultural factors, individuals from different countries may demonstrate varying propensities in choosing exercise methods.…”
Section: Discussionmentioning
confidence: 99%
“…The latest network meta-analysis reveals that CF multicomponent exercises may be the most effective strategies to improve cognitive function and frailty. 59 Future randomised controlled trials should be designed and evaluated based on both effectiveness and feasibility. Due to cultural factors, individuals from different countries may demonstrate varying propensities in choosing exercise methods.…”
Section: Discussionmentioning
confidence: 99%
“…30 Aerobic exercise, Baduanjin exercise, Otago exercise, and diverse integrative exercise have all been shown to delay and reverse cognitive frailty by improving patients' motor and cognitive functions. [31][32][33] Exercise interventions can improve patients' muscle status by reducing their C-reactive protein, reducing inflammation, improving their myocyte growth, and increasing muscle strength and endurance. 34 Exercise also affects structural plasticity in subregions of the hippocampus, such as the left parietal tract, right angular gyrus 1, and anterior inferior tract, which play a very important role in cognition, thus improving cognitive function.…”
Section: Analysis Of Factors Influencing Cognitive Frailty In Elderly...mentioning
confidence: 99%
“…Previous studies indicated that CF could be reversible [ 13 ], thus, identifying and responding to risk factors for CF can help to slow down or even reverse its progression. However, the associated factors discovered in current studies of CF, such as age, education level, etc., are not intervenable [ 14 ]. A review shows that social status, nutrition status, physical and cognitive activities and functional status are factors shown to be associated with CF [ 15 ].…”
Section: Introductionmentioning
confidence: 99%